2015
DOI: 10.1007/s10803-015-2430-9
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Well-Being in Parents of Children with Autism Spectrum Disorders (ASD)

Abstract: This study examined psychological well-being and coping in parents of children with ASD and parents of typically developing children. 73 parents of children with ASD and 63 parents of typically developing children completed a survey. Parents of children with ASD reported significantly more parenting stress symptoms (i.e., negative parental self-views, lower satisfaction with parent-child bond, and experiences of difficult child behaviors), more depression symptoms, and more frequent use of Active Avoidance cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
142
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(174 citation statements)
references
References 59 publications
(131 reference statements)
18
142
1
13
Order By: Relevance
“…Nikmat, Ahmad, Oon, and Razali (2008) found that 53.8% of Malaysian parents of children with autism showed a clinical disturbance in psychological wellbeing, conceptualised as clinically elevated scores on the General Health Questionnaire (GHQ-28), and 90.4% of parents demonstrated significant parenting stress on the Parenting Stress Index -Short Form (PSI-SF). Comparatively, similar parenting stress mean scores were found in a recent quantitative study in Singapore (Lai, Goh, Oei, & Sung, 2015). Lai et al (2015) utilised the Depression Anxiety Stress Scales (DASS-21) to measure the psychological wellbeing of parents, finding higher scores in parents of children with ASD than in parents of typically developing children.…”
Section: Wellbeing Of Parents Of Children With Asd In the Malaysian Csupporting
confidence: 58%
See 3 more Smart Citations
“…Nikmat, Ahmad, Oon, and Razali (2008) found that 53.8% of Malaysian parents of children with autism showed a clinical disturbance in psychological wellbeing, conceptualised as clinically elevated scores on the General Health Questionnaire (GHQ-28), and 90.4% of parents demonstrated significant parenting stress on the Parenting Stress Index -Short Form (PSI-SF). Comparatively, similar parenting stress mean scores were found in a recent quantitative study in Singapore (Lai, Goh, Oei, & Sung, 2015). Lai et al (2015) utilised the Depression Anxiety Stress Scales (DASS-21) to measure the psychological wellbeing of parents, finding higher scores in parents of children with ASD than in parents of typically developing children.…”
Section: Wellbeing Of Parents Of Children With Asd In the Malaysian Csupporting
confidence: 58%
“…Comparatively, similar parenting stress mean scores were found in a recent quantitative study in Singapore (Lai, Goh, Oei, & Sung, 2015). Lai et al (2015) utilised the Depression Anxiety Stress Scales (DASS-21) to measure the psychological wellbeing of parents, finding higher scores in parents of children with ASD than in parents of typically developing children. Lai et al (2015) highlighted the paucity of research in parental wellbeing among Asian parents of children with ASD living in Asian countries.…”
Section: Wellbeing Of Parents Of Children With Asd In the Malaysian Csupporting
confidence: 58%
See 2 more Smart Citations
“…In this regard, the literature identifies as protective factors the quality of coping strategies employed and familial relationships and the social support received (Hebert and Koulouglioti 2010;Lai et al 2015;Lai and Oei 2014;Zablotsky et al 2013).…”
Section: Introductionmentioning
confidence: 99%